Incorporating the morphological difference of corrosion cracks in computational fracture mechanics approach - Prawoto, Yunan (Elsevier B. V, 2012)
This paper encourages materials scientists to incorporate computational approach in their research. At the same time it gives a warning on how to use it, especially for stress corrosion cracking (SCC), since any continuum approach is highly dependent upon the shape of the crack. Evaluating the basic morphology of the SCC behavior of steels shows that each microstructure produces unique shape that can be used as a foundation for computational model creation.